Clinical and demographic study of scrub typhus in a tertiary care teaching hospital in Puducherry during 2015-2018 - Sariga, I.; Karthik, S. S.; Ratnam, P. Vivian Joseph (International Journal of Research in Medical Sciences, 2018)
Background: Scrub typhus is a vector borne rickettsial disease commonly found in many parts of India. Scrub typhus can frequently cause complications like pneumonia, acute respiratory distress syndrome (ARDS) and has a mortality rate of 30 to 45% in untreated cases. Diagnosis of scrub typhus is difficult, with serum IgM capture ELISA being the most sensitive test. Present study objectives were to study the clinical and demographic profiles of scrub typhus cases in a tertiary care teaching hospital in the Union Territory of Puducherry, India. Methods: A descriptive study was carried out to analyze clinical and demographic profiles of patients who were positive for IgM antibodies against Orientia tsutsugamushi by scrub typhus IgM ELISA during a three year period (April 2015 to March 2018). Demographic details like age and sex of the patients, clinical signs, symptoms and complication if any were analyzed. Results: A total of 428 patients were found to have been diagnosed with scrub typhus during the study period. Among them, 46% were males and 54% were females. Among all the positive cases, 23.5% were paediatric cases, the second highest group was the 31 to 40 years age group (17.7%). Thirteen percent of positive cases were above 60 years of age. Fever was the most common symptom (92.9%) and eschar was found in 22.9% of patients. The most common complication found in the patients with scrub typhus was acute respiratory distress syndrome (15.9%). Other complications like hepatic dysfunction, pleural effusion and meningoencephalitis were noted. Conclusions: Adequate knowledge about scrub typhus helps in early diagnosis, which facilitates early appropriate antibiotic and supportive therapy, which helps in the recovery of the patient without acquiring complications.